Tanycyte-Independent Control of Hypothalamic Leptin Signaling - Yoo, Sooyeon; Cha, David; Kim, Dong Won; Hoang, Thanh V.; Blackshaw, Seth (Frontiers in Neuroscience, 2019)
Leptin is secreted by adipocytes to regulate appetite and body weight. Recent studies have reported that tanycytes actively transport circulating leptin across the brain barrier into the hypothalamus, and are required for normal levels of hypothalamic leptin signaling. However, direct evidence for leptin receptor (LepR) expression is lacking, and the effect of tanycyte-specific deletion of LepR has not been investigated. In this study, we analyze the expression and function of the tanycytic LepR in mice. Using single-molecule fluorescent in situ hybridization (smfISH), RT-qPCR, single-cell RNA sequencing (scRNA-Seq), and selective deletion of the LepR in tanycytes, we are unable to detect expression of LepR in the tanycytes. Tanycyte-specific deletion of LepR likewise did not affect leptin-induced pSTAT3 expression in hypothalamic neurons, regardless of whether leptin was delivered by intraperitoneal or intracerebroventricular injection. Finally, we use activity-regulated scRNA-Seq (act-Seq) to comprehensively profile leptin-induced changes in gene expression in all cell types in mediobasal hypothalamus. Clear evidence for leptin signaling is only seen in endothelial cells and subsets of neurons, although virtually all cell types show leptin-induced changes in gene expression. We thus conclude that LepR expression in tanycytes is either absent or undetectably low, that tanycytes do not directly regulate hypothalamic leptin signaling through a LepR-dependent mechanism, and that leptin regulates gene expression in diverse hypothalamic cell types through both direct and indirect mechanisms.